How modern working environments shape attendance behaviour: A longitudinal study on weekly flexibilization, boundaryless work and presenteeism - Ute Poethke; Kai N. Klasmeier; Elvira Radaca; Stefan Diestel (Journal of Occupational and Organizational Psychology, 2023)
In the face of technological advancements, flexibilization and boundaryless work have become integral parts of modern occupational settings. Simultaneously, current research indicates a considerable increase in presenteeism—the behaviour of working while sick. Meta-analytic findings indicate two main drivers for presenteeism: a high work motivation and an impaired state of health and psychological well-being. Research on flexibilization and boundaryless work shows that these job conditions enhance employees' work motivation but also impair employees' health. Based on conservation of resources theory and Miraglia and John's (J Occupational Health Psychol, 21, 2016, 261) dual-path model on antecedents of presenteeism, we investigate how both job conditions affect attendance behaviour (absenteeism and presenteeism) via motivation and well-being by conducting a weekly diary study over the course of 90.167emweeks. In total, 284 people provided data on flexibilization, boundaryless work, flow experience, well-being, absenteeism and presenteeism (N0.167em=0.167em22840.167emweek-level). Multilevel mediational analyses revealed that flexibilization prevents presenteeism, whereas boundaryless work can increase presenteeism. The results further revealed support for the health impairment path at the within-person and between-person levels whereas the motivational path was not supported at the within-person level. Our results offer several theoretical and practical implications for how modern work shape attendance behaviour.
Keywords: 650; boundaryless work; diary study; flexibilization; multilevel investigation; presenteeism